Adherence to Therapeutic Recommendations in Patients with Type 2 Diabetes - Sylwia Krzemińska; Milan Laurinc; Ewelina Bąk; Mária Sováriová Soósová; Bogusława Kupczak-Wiśniowska (Kazimierz Wielki University, 2024)
Introduction: The level of modern medicine has led to a continuous extension of life expectancy. This fact is also linked to the aspect of proper adherence by patients to therapeutic recommendations. This process also applies to patients with diabetes, where it is often necessary to take multiple medications and adhere to a therapeutic regimen. However, the literature reports non-adherence to the prescribed therapy by patients. This behavior is so common and significant that the World Health Organization (WHO) included non-adherence to these recommendations in the list of the most serious health problems facing society, which is an obstacle in achieving positive outcomes of the therapy. Objective: The aim of the study is to evaluate the adherence to therapeutic recommendations in patients with type 2 diabetes. Materials and Methods: A total of 105 patients participated in the study, but due to missing responses, 98 correctly completed surveys were included in the analysis. The method used in the study was a diagnostic survey using a questionnaire. A standardized tool, the Adherence in Chronic Diseases Scale (ACDS), was used, and sociodemographic and clinical data were obtained from medical records and patient interviews. Summary Results: In the studied group, the average score on the ACDS scale was 19.29±3.85, which indicates a low level of adherence to therapeutic recommendations. Among women, adherence to recommendations averaged 19.83±3.46, while among men the average was lower at 18.46±4.29. However, these differences were not statistically significant (p > 0.05). Women only slightly adhered to medical recommendations more than men. In terms of adherence, groups distinguished by the duration of diabetes differed significantly (p < 0.05). There were significant statistical differences (p < 0.05) between individuals who had been ill for up to 20 years and those who had been ill for over 35 years. Half of the individuals who had been ill for up to 20 years adhered to medical recommendations at least as much as Me = 21.00, while half of those over 35 years adhered no more than Me = 18.00. Individuals who had been ill for up to 20 years adhered significantly more to medical recommendations than those who had been ill for over 35 years (p < 0.05). Conclusions: The study group is characterized by a low degree of adherence to therapeutic recommendations. Gender does not influence the level of adherence. The longer the duration of the disease, the lower the degree of adherence to therapeutic recommendations.